Hypopharyngeal evaluation in obstructive sleep apnea with awake flexible laryngoscopy: Validation and updates to Cormack‐Lehane and Modified Cormack‐Lehane scoring systems. (5th February 2018) - Torre, C.; Zaghi, S.; Camacho, M.; Capasso, R.; Liu, S. Y.
Abstract : Objective: To validate the use of Cormack‐Lehane and Modified Cormack‐Lehane scoring systems to classify patterns of hypopharyngeal airway visualization seen during awake flexible laryngoscopy among patients with obstructive sleep apnoea. Study design: Validation study using samples collected from a prospective database. Setting: University Medical Center. Participants: Data were obtained from a retrospective review of a prospective database of flexible fiberoptic examination recordings in 274 consecutive OSA subjects (Stanford Sleep Medicine/Surgery Clinic). Main outcome measures: Single still images from awake fiberoptic laryngoscopy examinations of the vocal cords from 90 different patients were presented to 2 experts and 4 novice raters. Raters used two grading systems (Cormack‐Lehane scale and Modified Cormack‐Lehane) to rate vocal cord visualization. Percent agreement and Cohen's kappa statistical analysis were used to evaluate inter‐rater reliability and intrarater reliability for each grading system. Feedback from the participants was then used to propose updates to further improve upon the existing grading scales for their applicability to awake flexible endoscopy. Results: The Cormack‐Lehane and Modified Cormack‐Lehane scale both communicate unobstructed and restricted views of the vocal cords reliably. Compared to the 4‐grade scale, however, a modified 5‐grade Vocal Cord Grading System allows for better objective communication of common variations in hypopharyngeal airway visualization. Conclusion: We propose a 5‐Grade Vocal Cord Grading System that builds upon existing grading systems to allow for efficient and reliable communication of hypopharyngeal airway examination during awake fiberoptic laryngoscopy.